Evaluator’s alignment as an important indicator of adequacy of the criteria and assessment procedure for recognizing the good practice in public health - Vinko, Matej; Lesnik, Tina; Radoš Krnel, Sandra (Frontiers in Public Health, 2024)
Background: Public health interventions aim to reduce the burden of chronic non-communicable diseases. Implementing evidence-based interventions that are proven to be successful and effective is widely recognized as the best approach to addressing public health challenges. To avoid the development and implementation of less effective or successful or even harmful practices, clear criteria for the assessment of practices that are considering different dimensions of the interventions in public health, are needed. The main aim of our research was to test our Criteria and assessment procedure for recognizing good practices in the field of public health by estimating the consistency between the evaluators and thereby gaining insight into the adequacy and reliability of the criteria as well as to check how the evaluators understand the criteria and methodology and if it is properly used in assessing the interventions. Methods: The assessment of the interventions took place from 2021 to 2022. The individual evaluator's scores on the scale from 1 to 5 for each specific sub-criterion were collected, which was followed by a panel discussion to reach a final score for each sub-criterion. The interrater agreement was measured using percent overall agreement and Fleiss's kappa coefficient. Results: We found moderate interrater agreement on the level of the assessment criteria group. The lowest agreement was observed for the effectiveness and efficiency sub-criteria group, which also received the lowest scores from the evaluators. Challenges identified with the scoring process were due to the descriptive 1 to 5 scale and the varying specificity of the criteria. Conclusions: The results showed that studying consistency between evaluators can highlight areas for improvement or adjustment in the assessment criteria and enhance the quality of the assessment instrument. Therefore, such analysis would be useful part of both newly and well-established Health promotion and prevention programme registries.